Aspectos morfológicos, reológicos e fisiológicos dos cultivos de Escherichia coli recombinante - Silva, Gabriel Gonçalves (2015)
The use of Escherichia coli cultures to obtain heterologous proteins poses as a successful application of biotechnology for the production of drugs and enzymes. However, the stress caused by the synthesis of the recombinant protein as well as by the culture conditions may trigger physiological responses on the cell and also cause changes in the cell morphology, impacting on the rheology of the culture broth. This study aimed to evaluate changes in cell morphology, on the rheology of the broth and the effect of different temperatures and inducers in the cellular responses during recombinant protein production by E. coli in batch cultures. Five medium cell density cultures were conducted with two clones of rE. coli, using defined medium containing glycerol as main carbon source and different inducers (IPTG and lactose), at two different temperatures (37°C and 27°C). All experiments were performed in 5 L bench bioreactor, equipped with a monitoring and control system. Samples were collected throughout the experiments and rheological parameters were measured using a concentric cylinder rheometer. The morphological characteristics of the microorganism were also examined by optical microscopy associated with image analysis. The concentrations of cellular suspension (optical density and dry cell weight) as well as of sugars and metabolites (HPLC), the plasmid retention (subculture on plates with and without antibiotic), the concentration of viable cells (colony forming units), the production of recombinant protein (densitometry), the concentration of soluble proteins (Bradford protein assay) and the presence of polysaccharide in the broth (phenol–sulfuric method) were also monitored. It was found that broths, initially behaving as Newtonian fluids, undergo a change in rheological behavior during the growth phase, exhibiting a Bingham fluid behavior. During the induction phase, the consistency index and the initial shear stress seemed to follow the changes in cell concentration or the stress caused by the protein synthesis, respectively. In addition, the intensity of the variation of both rheological parameters seemed to be dependent upon the used inducer. The morphology analysis showed that rheological properties could not be explained by changes in cell length. The correlation between the cell concentration (measured by dry-weight method) and the optical density when lactose was employed as inducer, due to galactose accumulation within the cells as a result of the inability of the bacteria to metabolize this carbon source. The presence of a small amount of PspA and genetic material in the culture broth was probably due to permeabilization and lysis of a small part of the population. Carbon recovery analysis was performed for all cultures, leading to values close do 100 % before induction, in all studied cases. After induction, a sharp decrease on the recovery was observed. However, by including the carbon present in the polysaccharide quantified in the cultivation broth, it was possible to recover all supplied carbon as biomass, CO2 and polysaccharide. Finally, the highest production of protein was obtained at 37°C when induced by IPTG, reaching 125 mgPspA/gMS. The results contribute to a deeper understanding of the heterologous proteins production by rE. coli and allow the definition of intensification strategies for protein production.